2008
DOI: 10.1029/2007jd008503
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of Greenland winter precipitation sources: Lagrangian moisture diagnostic and North Atlantic Oscillation influence

Abstract: [1] We present a new Lagrangian diagnostic for identifying the sources of water vapor for precipitation. Unlike previous studies, the method allows for a quantitative demarcation of evaporative moisture sources. This is achieved by taking into account the temporal sequence of evaporation into and precipitation from an air parcel during transport, as well as information on its proximity to the boundary layer. The moisture source region diagnostic was applied to trace the origin of water vapor for winter precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
793
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 422 publications
(823 citation statements)
references
References 47 publications
24
793
6
Order By: Relevance
“…The intensity of these uptakes preceding the precipitation is reduced since they contribute less to the moisture arriving in the area of interest. This procedure is explained in detail in Sodemann et al (2008), and has been applied successfully in several previous studies, for example, Sodemann and Zubler (2010), Winschall et al (2012Winschall et al ( , 2014.…”
Section: Moisture Source Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of these uptakes preceding the precipitation is reduced since they contribute less to the moisture arriving in the area of interest. This procedure is explained in detail in Sodemann et al (2008), and has been applied successfully in several previous studies, for example, Sodemann and Zubler (2010), Winschall et al (2012Winschall et al ( , 2014.…”
Section: Moisture Source Diagnosticsmentioning
confidence: 99%
“…Evaporative moisture sources of the precipitation event are calculated with the Lagrangian technique developed by Sodemann et al (2008). This technique considers 6-hourly changes of specific humidity q along backward trajectories from the considered area of precipitation and attributes positive changes of q with time to local moisture uptake due to surface evaporation.…”
Section: Moisture Source Diagnosticsmentioning
confidence: 99%
“…This is always an arbitrary choice, and most studies have chosen it in terms of a certain flux but did not provide information on how much moisture the area within a boundary receives as a percentage of the source region's evaporation (forward tracking) or precipitation (backward tracking) [e.g., Sodemann et al, 2008;Dirmeyer et al, 2009a ;Dominguez et al, 2009 ;Drumond et al, 2010 ;Gimeno et al, 2010]. We like to argue that this information is crucial in assessing the spatial extent of a source region's influence.…”
Section: Cautionary Notesmentioning
confidence: 99%
“…[4] Many of these atmospheric moisture tracking studies focused on a particular basin, country, or terrestrial region and identified the moisture sources or sinks for that region taking account of interannual or seasonal variability [e.g., Druyan and Koster, 1989;Numaguti, 1999;Yoshimura et al, 2004;Bosilovich and Chern, 2006;Nieto et al, 2006;Sodemann et al, 2008;Dominguez et al, 2009;Drumond et al, 2010;Gangoiti et al, 2011aGangoiti et al, , 2011bBagley et al, 2012;Keys et al, 2012;Tuinenburg et al, 2012]. More global characterizations of moisture sources showed the import and export of water vapor between nations [Dirmeyer et al, 2009a], or the oceanic versus terrestrial contributions to continental precipitation [e.g., van der Ent et al, 2010;Goessling and Reick, 2011] [5] Our own recent work [van der Ent et al, 2010;van der Ent and Savenije, 2011] showed that globally about 40% of the precipitation on land originates from continental rather than oceanic evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, the aim is to identify the leading moisture source regions for Alpine precipitation and to quantify their seasonal and inter-annual variability. The moisture sources are diagnosed from European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-40 reanalysis data, using the quantitative Lagrangian moisture source diagnostic by Sodemann et al (2008b). The use of a diagnostic method, as opposed for example to general circulation model simulations, has two advantages.…”
Section: Introductionmentioning
confidence: 99%